Men in menopause? Experimental verification of the mate choice theory with Drosophila melanogaster shows both sexes can undergo menopause - Divya Purohith; Mitali Chaudhary; Alyssa Gomes; Nina Rajapakse; Aditi Das; Neha Dhanvanthry; Michelle Brown; Manan Mukherjee; Rama S. Singh (PLoS ONE, 2025)
Various hypotheses regarding the origin of menopause have been proposed, and although the kin-selection-based theory appears promising, it involves population genetic processes that are insufficient to compensate for loss of fitness. The grandmother hypothesis and its variation the live long hypothesis is untenable; the former requires “climbing a steep fitness hill”, as grandmothers share only 25% of their genes with their grandchildren, compared to 50% with their direct offspring, while the latter proposes a prolongation of the post-menopausal lifespan through selection, which is not possible in a population of non-reproducing females. The mate choice theory explains menopause as the result of asymmetric mating involving younger females and older males that leads to an accumulation of infertility mutations and the evolution of menopause in older females. In this study, we investigated the mate choice theory using an infertility mutation accumulation experiment with Drosophila melanogaster that involved mating between individuals of different age groups. After 70 generations of asymmetric mating, the results showed that younger females who were paired with older males showed declining fertility in old age. The same trend was noted with younger males when mated with older females; the fertility of the males declined in old age. These results support the mate choice theory and indicate that menopause is not a life history trait of females but of the sex of the younger mate. Mate choice theory treats the evolution of menopause and post-menopausal lifespan as independent traits that are driven by the mate choices exercised by older males. Menopause may be an atypical process because the evolutionary mechanism (age-restricted asymmetric mating) involved is rarely observed in nature.